PEDAGANG KAKI LIMA PADA MASA KRISIS - Agus Joko Pitoyo (Populasi, 1999)
Based on a survey of 325 street vendors in Yogyakarta Special Region that was conducted by the Population Studies Center of Gadjah Mada University, this study would like to analyze the contribution of income and prospect of the informal sector on household economy. It was found that earning in the informal sector constitutes the source of household income. Most street vendors said that income in the informal sector would help them improve on the household economic status. Working as a street vendor is a good choice. It has a good prospect and can be developed in the future.This research has also shown that the informal sector is capable to survive in the crisis. Caused by more flexibility, the number of people absorbed in the informal sector are even able to earn higher incomes. This implies that providing access to informal sector with such a high commitment of both government and non- governmental institutions, it is one important policy in helping them have better conditions in a economic household. Accordingly, it will in turn have an impact on increasing the economic scale of the informal sector.